Pelatihan Pembelajaran Matematika Inovatif di Sekolah Dasar - Wahab, Abdul; Junaedi, Junaedi (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
Community service activities in the form of elementary mathematics learning training. This activity was carried out at SDN 032 Kebun Sari, Wonomulyo District, Polman Regency, West Sulawesi, Indonesia. Participants in the community service activities were elementary school mathematics teachers who were members of the Teacher Working Group in Wonomulyo District, Polewali Mandar Regency. The objectives of the community service activities are: (1) Increasing knowledge of innovative mathematics learning strategies for elementary school teachers; and (2) Increasing the knowledge of elementary school teachers about elementary math concept knowledge. Community service activities have increased elementary mathematics teachers' understanding of learning strategies and knowledge of elementary math concepts for math teachers in the Wonomulyo sub-district.